THE USE OF KOMPAS IN DETERMINING THE ACCURACY OF QIBLA DIRECTION (CASE STUDY ON MOSQUES IN SERDANG BEDAGAI REGENCY) - Muhammad Habibul Amin; Dhiauddin Tanjung; Hasan Matsum (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the level of accuracy of the direction of the Qibla in several mosques in Serdang Bedagai Regency which is determined using a compass, by comparing it to the direction of the Qibla calculated astronomically using geographic coordinate data and the help of GPS-based digital applications (such as Google Earth). The scholars agree that people who can see the Kaaba directly must face the Kaaba building ('ainul Kaaba). However, for people who are outside the Grand Mosque, especially far from Mecca, it is sufficient to face the Kaaba (Jihah Kaaba). Determining the accurate direction of the Qibla is important in carrying out Islamic prayers. In various regions, including Serdang Bedagai Regency, the method commonly used by people to determine the direction of the Qibla is using a compass. However, the accuracy of the compass is often influenced by environmental factors such as local magnetic fields and inaccuracy in use. This study uses an empirical Islamic legal research method (non-doctrinal research), a legal research method that functions to see how the law works in society. The object of the study is the direction of the Qibla from mosques in Serdang Bedagai Regency, totaling 665 mosques which are the research population. The sample in this study was 17 mosques from several sub-districts using the Purposive Sample technique which is a non-random sampling technique, with the vastness of Serdang Bedagai Regency and the large number of mosques requiring researchers to conduct non-probability sampling. In addition, researchers also conducted interviews. The results of the study showed that there was a deviation in the direction of the Qibla in most mosques with an average difference of 2° to 25° from the actual direction. This shows that the use of a compass manually without calibration and consideration of local factors can cause inaccuracy in determining the direction of the Qibla. This study recommends the use of more precise methods such as GPS devices, digital applications, or observations of the position of the sun during Rashdul Qiblah, especially for the construction of new mosques.